2002
DOI: 10.1038/sj.jhh.1001305
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effects of chronic ACE inhibition and AT1 receptor blocked losartan on cardiac hypertrophy and renal function in hypertensive patients

Abstract: The present study describes the effects of losartan and the angiotensin-converting enzyme inhibitor enalapril on blood pressure, echocardiographically calculated left ventricular mass, renal function evaluated by glomerular filtration rate and quality of life. The renin-angiotensin-aldosterone system is of importance for cardiovascular growth. There is substantial experimental documentation in animals that the angiotensin II antagonist, losartan, decreases the cardiac hypertrophy response caused by elevated ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 17 publications
2
31
0
1
Order By: Relevance
“…In transgenic animal models, increased AT1R expression in the myocardium is sufficient to initiate hypertrophic growth (11,12). Furthermore, AT1R antagonist treatment prevents the development of cardiac hypertrophy in experimental animal models and in hypertensive patients (13).…”
Section: Rab1mentioning
confidence: 99%
“…In transgenic animal models, increased AT1R expression in the myocardium is sufficient to initiate hypertrophic growth (11,12). Furthermore, AT1R antagonist treatment prevents the development of cardiac hypertrophy in experimental animal models and in hypertensive patients (13).…”
Section: Rab1mentioning
confidence: 99%
“…27 ACE plays an important role in the physiology and pathophysiology of humans at high altitude 28 probably through its effects on skeletal muscle, 29 cardiac function, 30 sodium and fluid retention via the RAS, 31 and possibly on the respiratory center via the nucleus tractus solitarii as shown in a rat model. 32 ACE mRNA was highly expressed in pulmonary vessels of rats with high-altitude hypoxic pulmonary hypertension, 33 a sign indicating a failure in high altitude adaptation.…”
Section: Genotypic Distributions and Allelic Frequencies Of The Ace Imentioning
confidence: 99%
“…14,22,25,27,28,41,69,78,79,84,88,89,92 Apart from one study in which there was a greater reduction of left ventricular hypertrophy with an ARB, 89 there were no differences between ACE inhibitor and ARB groups. Only one study evaluated a DRI; it found similar effects between aliskiren and an ARB.…”
Section: Left Ventricular Mass or Functionmentioning
confidence: 99%
“…Thirty studies (11 new, including two evaluating a DRI) presented original results on either serum creatinine/ GFR, 13,19,22,28,33,43,59,72,82,87,91,92 proteinuria, 11,29,58,60,80,103 or both. 23,30,46,49,56,62,65,73,81,97,99,102 The ten new studies that described changes in creatinine or glomerular filtration rate did not consistently demonstrate differential effects with use of ACE inhibitors versus ARBs, nor did the two studies comparing a DRI with the ACE inhibitor ramipril; 11,13 these findings were similar to those from the 2007 report.…”
Section: Serum Creatinine Level Glomerular Filtration Rate and Protmentioning
confidence: 99%
See 1 more Smart Citation